Validity of Taylor's rule for Turkey: An empirical study - TOKEL, DİLEK (My University, 2021)
The aim of this paper is to propose an estimate of the reaction function of Turkey's monetary policy for the periods from January 2005 to January 2020. In this perspective, a VAR (Vector Autoregressive) model is set up. The VAR model was estimated using Stata software. In this study, the Taylor rule is extended by implicating the industrial production index and the monetary aggregate M2 into policy reaction function. By doing so, the Taylor rule is investigated for the Turkish economy, and the validity of the rule is tested. The results of the ADF test show for all the observed variables that the null hypothesis of a unit root is rejected. In other words, the condition of stationarity seems to be satisfied. In the short term, it seems that a change in the behavior of the variable M2 has an impact of 1% on the level of the current inflation rate as well as the current real interest rate. For the period studied, the results of the VAR modeling indicate that Taylor's rule is partly true for the short term but that it is not for the long term. The choice of the period studied seems to be the main reason for the non-cointegration between the inflation rate and the bank rediscount rate.
Validity of Taylor's rule for Turkey